Research on the Application of Grey Prediction Model in the Development of Cross-border E-commerce Platforms for Rural Revitalization - Liu, Tianning; Pang, Xinyu; Zuo, Hang (Journal of Global Economy, Business and Finance, 2025)
Current challenges in agricultural product sales include domestic oversupply, rural technical talent shortages, insufficient market information, and inadequate insurance measures. This study employs the grey prediction model to forecast the development of agricultural product economies under the “RedComplex” platform while integrating red cultural heritage. Methods: A differential equation model was established to analyze historical trends in e-commerce platform growth and project platform quantities for the next two years. A multiple linear regression model was further applied to assess the impact of national policies on China’s e-commerce development. Conclusions: The number of e-commerce platforms has surged in recent years, driven significantly by per capita disposable income and consumer confidence indices. Projections indicate 15 million platforms by 2025 and 20 million by 2026. Guided by the “Red Culture Empowering Agriculture” principle, integrated service platforms can enhance rural income. To remain competitive, the “RedComplex” platform requires multi-dimensional upgrades to foster industrial and cultural progress.